Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
New Advances on Fermentation Processes 2020
DOI: 10.5772/intechopen.87052
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Alkaline Fermented Foods and Seasoning Agents of Africa

Abstract: Fermented foods and seasoning agents play central roles in the food and nutrition security of nations across the world, but particularly so in Africa, Asia, South America and Oceania. As several people across the world gravitate back to "eating natural," there is a new emphasis on these fermented foods and seasoning agents which are also critical cultural foods in countries and societies where they are important. The result is the growth in demand for these products beyond what the traditional kitchen technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Examples of alkaline fermented foods produced from plant seeds are Dawadawa/Soumbala (African locust bean), Dawadawa-type product (Bambara groundnut; Vigna subterranea), Ogiri Owoh (Melon, Citrullus vulgaris L. and Cottonseed, Gossypium hirsutum L.), Owoh (African yam bean, Sphenostylis stenocarpa), Ogiri (Castor oil bean, Ricinus communis), Bikalga (Roselle; Hibiscus sabdariffa), Ugba (African oil bean seeds, Pentaclethra macrophylla), Aisa (rain tree or saman tree, Albizia saman), Okpehe/kpaye/okpiye (African mesquite, Prosopis africana), etc. (Nurudeen and Chimezie Okorie, 2019) (Ugwuanyi and Okpara, 2020). In this present study, Bacillus was found to dominate the microbiota of Kahudi.…”
Section: Discussionsupporting
confidence: 60%
“…Examples of alkaline fermented foods produced from plant seeds are Dawadawa/Soumbala (African locust bean), Dawadawa-type product (Bambara groundnut; Vigna subterranea), Ogiri Owoh (Melon, Citrullus vulgaris L. and Cottonseed, Gossypium hirsutum L.), Owoh (African yam bean, Sphenostylis stenocarpa), Ogiri (Castor oil bean, Ricinus communis), Bikalga (Roselle; Hibiscus sabdariffa), Ugba (African oil bean seeds, Pentaclethra macrophylla), Aisa (rain tree or saman tree, Albizia saman), Okpehe/kpaye/okpiye (African mesquite, Prosopis africana), etc. (Nurudeen and Chimezie Okorie, 2019) (Ugwuanyi and Okpara, 2020). In this present study, Bacillus was found to dominate the microbiota of Kahudi.…”
Section: Discussionsupporting
confidence: 60%
“…Generally, Bacillus spp. are the principal microorganisms that drive the fermentation of African locust beans (Olasupo and Okorie, 2019;Ugwuanyi and Okpara, 2020). Studies have revealed that the hypotensive effects of African locust bean are mainly contributed by phenolic and flavonoid compounds.…”
Section: Antihypertensive Effects Of Fermented African Locust Beanmentioning
confidence: 99%
“…A very old preservation method is fermentation or ensilaging based on the use of naturally present or added lactic acid bacteria that can convert carbohydrates into lactic acid and other organic acids, resulting in a pH reduction . Next to acidic fermentations, alkaline fermentation by Bacillus or fungi can occur . For some Bacillus strains, alkaline fermentation led to a loss of protein functionality as a result of protein denaturation .…”
Section: Mechanisms Of Stabilizationmentioning
confidence: 99%